1990
DOI: 10.1128/jb.172.6.3435-3443.1990
|View full text |Cite
|
Sign up to set email alerts
|

Studies of sigma D-dependent functions in Bacillus subtilis

Abstract: Gene expression in Bacillus subtilis can be controlled by alternative forms of RNA polymerase programmed by distinct a factors. One such factor, SD ((r28), is expressed during vegetative growth and has been implicated in the transcription of a regulon of genes expressed during exponential growth and the early stationary phase. We have studied several functions related to flagellar synthesis and chemotaxis in B. subtilis strains in which ufD is missing or is present at reduced levels. Previous studies showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
143
0
2

Year Published

1991
1991
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(150 citation statements)
references
References 49 publications
5
143
0
2
Order By: Relevance
“…Marquez et al (30) found that the lack of &'P causes a decrease in the amounts of major autolysin (amidase) and glucosaminidase. Therefore, the sin (flaDl) mutation might interfere with transcription from the Pd promoter by depressing expression of sigD.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Marquez et al (30) found that the lack of &'P causes a decrease in the amounts of major autolysin (amidase) and glucosaminidase. Therefore, the sin (flaDl) mutation might interfere with transcription from the Pd promoter by depressing expression of sigD.…”
Section: Resultsmentioning
confidence: 99%
“…B. subtilis AD2 [purB his-i A(lppXcwlB)::cat] was constructed as described below and used as a host for promoter probing. Pleiotropic mutants B. subtilis CB100 (sigD::pLM5 trpC2 cat) (kindly provided by Michael J. Chamberlin [30]) and B. subtilis AC334 (purB sin [flaDI lyt-1]) (1) were also used. The sin (flaDI) mutation is a GAT-to-GGT change at codon 84, causing an Asp-to-Gly amino acid substitution in Sin (FlaD) (26).…”
Section: Materuils and Methodsmentioning
confidence: 99%
See 3 more Smart Citations